C. Vann Woodward : America's historian - Cobb, James C. (James Charles), 1947- (The University of North Carolina Press, 2022)
"With an epic career that spanned two-thirds of the twentieth century, C. Vann Woodward (1908-1999) was a historian of singular importance. A brilliant writer, his work captivated both academic and public audiences. He also figured prominently in the major intellectual conflicts between left and right during the last half of the twentieth century, although his unwavering commitment to free speech and racial integration that affirmed his liberalism in the 1950s struck some as emblematic of his growing conservatism by the 1990s."-- Provided by publisher.
Keywords: Woodward, C. Vann -- (Comer Vann), -- 1908-1999.; Woodward, C. Vann -- (Comer Vann), -- 1908-1999; Historians -- United States -- Biography.; Southern States -- Historiography.; Historiens -- États-Unis -- Biographies.; États-Unis (Sud) -- Historiographie.; BIOGRAPHY & AUTOBIOGRAPHY / Historical; Historians; Historiography; Southern States; United States; Biographies